pH-sensitive fibronectin nanogels combined with UTMD for anti-atherosclerosis treatment through anti-inflammatory and antioxidant effects - Mengjiao Zhang; Xianghao Xiao; Xinyi Li; Xiangyang Shi; Zhaojun Li (Materials Today Bio, 2025)
The reactive oxygen species (ROS) and inflammatory factors secreted by macrophages play pivotal roles in all stages of atherosclerotic progression. Achieving targeted plaque localization while simultaneously reducing ROS levels to exert both anti-inflammatory and antioxidant effects remains a significant challenge. In this work, we developed a pH sensitive curcumin (Cur)-loaded fibronectin (FN) nanogels, combined with ultrasound-targeted microbubble destruction (UTMD) to enhance therapeutic efficacy via cavitation effects. The FN/FBA-PEG-FBA@Cur (denoted as FNC) nanogels demonstrated a targeted effect on atherosclerosis sites, attributed to the strong affinity between the RGD sequence on FN and the integrins highly expressed on the surface of plaque cells. Moreover, the Schiff base linkages in the nanogels respond to the acidic microenvironment within atherosclerosis plaques, leading to the controlled Cur release, which enable anti-inflammatory and antioxidant activity to attenuate plaque progression. Both in vitro and in vivo experiments confirmed enhanced suppression of plaque progression following treatments with FNC nanogels under UTMD. In summary, the FN nanogels capable of targeting to atherosclerosis plaques offers a promising therapeutic approach for atherosclerosis.